The Development of PBL-Based Respiratory App Learning Media on Human Respiratory System Material to Improve Critical Thinking Skills of Grade 11th Students - Hosniyah; Evy Yulianti; Ahmad Kamal Sudrajat; Hairiyah (Postgraduate, University of Mataram, 2023)
This research aims to develop a PBL-based Respiratory App learning media on human respiratory system material, and to asses the feasibility, practicability, and effectiveness of the PBL-based Respiratory App learning media to improve critical thinking skills of class XI students at SMAN 6 Yogyakarta. This research used the ADDIE model developed by Dick and Carry. ANOVA test was used to analyze data of critical thinking skills. The results of the feasibility of learning media from material expert lecturers obtained an average score of 3.0 with a decent category. Media feasibility assessment conducted by media expert lecturers obtained an average score of 3.8 with a very feasible category and practicability assessment from biology subject teachers obtained an average score of 3.5 with a very practical category. The results of the small group trial obtained an average score of 3.3 with a practical category. Field trials using quasi-experiments showed sig 0. 00, and the experimental class’s critical thinking skills significantly different from the control class. The N-gain score showed the experimental class value is higher than the control class. Based on the research results, it will be concluded as follows: 1) PBL-based Respiratory App learning media was feasible and practicable for use in the learning process. 2) PBL-based Respiratory App learning media effectively improves students' critical thinking